The Influencing Factors of The Leptospirosis Prevalence in the Working Area of the Kebonagung Public Health Center - Diaswati, Mellina Sukma; Marsanti, Avicena Sakufa; Ratnawati, Riska (Jurnal Ilmiah Kesehatan (JIKA), 2024)
Leptospirosis is an infectious disease in the world caused by the bacterium Leptospira sp. The Kebonagung Public Health Center reported 34 cases of leptospirosis in 2023. The purpose of the study is to determine the factors influencing the leptospirosis prevalence in the Working Area of the Kebonagung Public Health Center. The type of this research was quantitative using a case control study design. The number of samples obtained were 22 cases and 22 controls. The sampling technique used were non probability sampling with purposive sampling. Univariate data analysis construed the frequency distribution, bivariate analysis with Chi-square test, and multivariate analysis with logistic regression test. The results of the bivariate analysis shows that there is an influence between education (p-value=0,018), occupation (p-value=0,037), and past injury (p-value=0,003) on the prevalence of leptospirosis in the working area of the Kebonagung Public Health Center. There is no influence between income (p-value 0,280) and personal hygiene (p-value=0,203) on the leptospirosis prevalence in the working area of the Kebonagung Public Health Cente,. The results of multivariate analysis shows that the factor that most influenced the prevalence of leptospirosis in the working area of the Kebonagung Public Health Center, is past injuries with (p-value=0,006). It is hoped that the public will adopt clean and healthy living habits, especially in caring for wounds and with Increasing leptospirosis surveillance, cross-sectoral coordination, and also familiarization of leptospirosis prevention and control need to be conducted as soon as possible to prevent the prevalence of leptospirosis.